Improved antimicrobial activity of silica-Cu using a heteropolyacid and different precursors by sol-gel: synthesis and characterization - Arreche, Romina Andrea (2015)
Antimicrobial coatings are used to avoid the proliferation of fungi and bacteria inside urban buildings by incorporating low concentrations of antimicrobial agents (biocides). This study is focused on evaluating the antifungal activity of copper (II) supported on a silica matrix, and as counter-cation of a heteropolyacid, obtained from the sol-gel method using various catalysts, against two fungal isolates. The fungi used in this evaluation were Alternaria alternata and Chaetomium globosum isolated by routine microbiological techniques from biodeteriorated paints films. In all cases, fungi were selected due to their ability to grow on the paint films and their negative impact on human health. First, silicas were prepared using tetraethylorthosilicate and methyl trimethoxysilane as precursors and acetic acid, hydrochloric acid as catalysts of the hydrolysis reaction of the alkoxide. The effect of addition of copper (II) in the form of copper nitrate was studied. With respect to the morphology of the silica, most of them are similar, between pure and modified silica, in all cases. Once the stage of the synthesis and characterization of the prepared materials was performed, six of them were selected to evaluate their antifungal activity by agar plate inhibition test against both fungi of interest (A. alternata and C. globosum), and the percent inhibition was determined in each case. Tested Cu-based solids were shown to have a higher antifungal activity because they completely inhibit the growth of both fungi with lower concentrations relative to its control. This work was performed as a preliminary study, in order to guide the selection of a suitable organic biocide from a list of possible antifungal agents.